Limonium divaricatum (Plumbaginaceae), the Arabian Phoenix of sea-lavenders - Erben, Matthias; Del Guacchio, Emanuele (Phytotaxa, 2021)
Limonium divaricatum has been regarded for a long time the name of a taxon occurring in the main islands of western Mediterranean, or as a mere synonym of L. virgatum. In this paper, a critical review of literature and herbarium data allows us to reduce L. divaricatum to a synonym of L. dubium; the lectotypification of this latter name is also amended.